FAPI-04 PET/CT Using [18F]AlF Labeling Strategy: Automatic Synthesis, Quality Control, and In Vivo Assessment in Patient - Jiang, Xiao; Wang, Xiaoxiong; Shen, Taipeng; Yao, Yutang; Chen, Meihua; Li, Zeng; Li, Xiuli; Shen, Jiaqi; Kou, Ying; Chen, Shirong; Zhou, Xing; Luo, Zhifu; et al. (Frontiers in Oncology, 2021)
68Ga labeled FAPI is the current standard for FAPI-PET, but its batch activity is limited. [18F]AlF-NOTA-FAPI-04 is a promising alternative combining the advantages of a chelator-based radiolabeling method with the unique properties of fluorine-18. The objective of this study was to develop a quick automatic method for synthesis of [18F]AlF-NOTA-FAPI-04 using a AllinOne synthesis system, and perform PET imaging with [18F]AlF-NOTA-FAPI-04 on patients. [18F]AlF-NOTA-FAPI-04 was produced and its quality control was conducted by HPLC equipped with a radioactive detector. [18F]AlF-NOTA-FAPI-04 PET/CT imaging was performed in normal BALB/c mice (n=3) and 4T1 breast cancer models (n=3) to determine its biodistribution. Then [18F]AlF-NOTA-FAPI-04 and 18F-fluorodeoxyglucose (FDG) PET/CT imaging were performed in an invasive ductal carcinoma patient (female, 54 years old). The synthesis time of [18F]AlF-NOTA-FAPI-04 was about 35 min, and the radiochemical yield was 25.2±1.9% (attenuation correction, n=3). The radiochemical purity was above 99.0% and was above 98.0% after 6 h. The product was colorless transparent solution with pH value of 7.0-7.5,and the specific activity was 46.11±3.07 GBq/μmol. PET/CT imaging in mice showed that physiological uptake of [18F]AlF-NOTA-FAPI-04 was mainly in biliary system and bladder, and [18F]AlF-NOTA-FAPI-04 highly concentrated in tumor xenografts. PET/CT imaging in the patient showed that [18F]AlF-NOTA-FAPI-04 obtained high tumor background ratio (TBR) value of 8.44 in segment V and VI, while TBR value was 2.55 by 18F-FDG. [18F]AlF-NOTA-FAPI-04 could be synthesized with high radiochemical yield and batch production by AllinOne module and show excellent diagnosis performance in cancer patients.